Application of medical products: mandatory requirements, supervision of their compliance - O. A. Makhova (Фармакоэкономика)
Background. Specific features of medical products (MPs), their active development and implementation in healthcare require post-market control and safe use.Objective: to study the existing state regulation in the field of medical products, methods of state control, self-control in medical organisations for their use.Material and methods. Regulatory legal acts of the Russian Federation defining mandatory requirements, control over the use of MPs were analyzed. Indicators of Federal Service for Surveillance in Healthcare (Roszdravnadzor) in this area were studied. A survey of medical professionals on the safe use of MPs was conducted, the answers of 343 respondents were evaluated.Results. The analysis of regulatory legal acts shows that, unlike with medicines, biomedical cellular products, when it comes to MPs application requirements, methods of use are not sufficiently specified. State control over the circulation of MPs is generally structured and regulated. The main ways of modern state control are the introduction of a risk-oriented approach to conducting scheduled inspections since 2018, the introduction of a mechanism to control purchases of medical services and products. Typical violations identified by Roszdravnadzor in medical organisations are the use of unregistered or substandard MPs. Also, a frequent violation is a failure to report (or untimely communication) to Roszdravnadzor about undesirable reactions when using MPs. State regulator has developed and approved a mandatory procedure for internal control of quality and safety of medical practice, including control over the storage and use of MPs. At the same time, according to the results of the survey, managers are not sufficiently informed on where to take up-to-date information that the MPs need to be stopped using. Additionally, the survey confirmed that representatives of medical organizations administrations know less than doctors about poor quality MPs in the clinic. Another finding of the survey was that the frequency of unwanted reactions to the application of MPs is significant, but the amount of reporting to the regulator is insufficient. This situation increases the risk of harm to the life and health of patients. In addition, there is a significant frequency of incidents in the use of MPs, with very little reporting to Roszdravnadzor from medical organizations.Conclusion. Further improvement of regulation in the field of MPs circulation at the post-registration stage, strengthening of control, primarily internal, over their safe and effective use are necessary.